A Theory of Instrument-Specific Absolute Pitch - Reymore, Lindsey; Hansen, Niels Chr. (Frontiers in Psychology, 2020)
While absolute pitch (AP)—the ability to name musical pitches globally and without reference—is rare in expert musicians, anecdotal evidence suggests that some musicians may better identify pitches played on their primary instrument than pitches played on other instruments. We call this phenomenon “instrument-specific absolute pitch” (ISAP). In this paper we present a theory of ISAP. Specifically, we offer the hypothesis that some expert musicians without global AP may be able to more accurately identify pitches played on their primary instrument(s), and we propose timbral cues and articulatory motor imagery as two underlying mechanisms. Depending on whether informative timbral cues arise from performer- or instrument-specific idiosyncrasies or from timbre-facilitated tonotopic representations, we predict that performance may be enhanced for notes played by oneself, notes played on one’s own personal instrument, and/or notes played on any exemplar of one’s own instrument type. Sounds of one’s primary instrument may moreover activate kinesthetic memory and motor imagery, aiding pitch identification. In order to demonstrate how our theory can be tested, we report the methodology and analysis of two exemplary experiments conducted on two case-study participants who are professional oboists. The aim of the first experiment was to determine whether the oboists demonstrated ISAP ability, while the purpose of the second experiment was to provide a preliminary investigation of the underlying mechanisms. The results of the first experiment revealed that only one of the two oboists showed an advantage for identifying oboe tones over piano tones. For this oboist demonstrating ISAP, the second experiment demonstrated that pitch-naming accuracy decreased and variance around the correct pitch value increased as an effect of transposition and motor interference, but not of instrument or performer. These preliminary data suggest that some musicians possess ISAP while others do not. Timbral cues and motor imagery may both play roles in the acquisition of this ability. Based on our case study findings, we provide methodological considerations and recommendations for future empirical testing of our theory of ISAP.